FITNESS USERS' KNOWLEDGE AND ATTITUDE TOWARDS FITNESS - Đorđe Nićin; Velimir Vukajlović; Nataša Trivić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Today, Fitness has become a phenomenon. It is a modern, cultivating movement that involves a lot of people of both genders,various ages, proffesions and affinities. The basic purpose of this research is the information gathering of Fitness practi- tioners' knowledge and attitude towards Fitness. Using the Likert scale, an anonymous survey was conducted on the exampler of 91 fitness users in order to get the information on their knowledge about fitness. Based on the knowledge questionnare, next step was to analyse the attitude of users as well as to understand the relationship between the know- ledge and attitude of fitness users towards fitness.